Modelling Framework for Dynamic Multiclass Traffic Assignment in ITS Environment - Bošnjak, Ivan; Jusufranić, Ibrahim; Višnjić, Vinko (Promet - Traffic&Transportation, 2004)
Deployment of flexible traffic control, pre-trip, on-trip,guidance and other ITS services require considerable researchtoward the development of appropriate methodological frameworkand tools. In this paper, adapted modelling framework fordynamic mu/tic/ass traffic assignment (DMTA) in ITS environmentis proposed and elaborated. DMTA system uses trafficdata associated with three backdrops: time, space and defined’user classes’. The proposed structure of DMTA system includesmodules for 0-D estimation and prediction, real-timenetwork state simulation, consistency checking, updating functions,resetting functions. The methodological tools for solvingDMTA problems include combination of mathematical programming,simulation and heuristic methods.